FULL FACTORIAL ANALYSIS OF PARAMETERS USED FOR CRUDE OIL CLEANUP FROM CONTAMINATED SOIL USING ZNCL2 BASED DEEP EUTECTIC SOLVENT (DES) AS SOLVENT - E. A. AUDU; P. A. EKWUMEMGBO; S. UBA; . M. ENGAH, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
A new strategy of crude oil cleanup from contaminated soil using synthesized DES based on zinc chloride/acetamide was studied. The ability for cleaning up crude oil from soil was investigated under different condition and was optimized using full factorial design of experiment. Physiochemical analysis of synthesized DES showed viscosity to be 26.0cp at 28 °C, pH was found to be 5.4, density was 1.32 g/cm3 and the flammability test confirmed the solvent to be nonflammable. Factors considered for the optimization of cleanup include solvent volume, temperature and contact time. Experiment was carried out in duplicates generating 16 runs giving percentage yields of 40%,54%,58%, 56%, 44%, 56%, 28%, 78%, 41%, 54%, 58%, 54% 48%, 60%, 32% and 81% from standard run order of 1- 16 respectively. From the results, run 16 gave the best yield of 81% with optimal conditions (A+ B+ C+) at 25 mL solvent volume, 120°C temperature and 30 min contact time. Run 7 gave the least yield of 28%. Results were subjected to various analyses using Minitab 18.0 to find significant factors, effect of factors and interactions. Analysis of variance (ANOVA) showed that at SV and T were significant factors at p = 0.05. However, CT was statistically not significant at the same confidence level. Perato chart ranked the order of factor and interaction effect as: SV > SV*T*CT > SV*CT > T > SV*T > T*CT > CT with SV being the most effective factor and CT being the least effective at P = 0.05. Main effect analysis showed that SV is the most significant factor with individual effect of 61% yield followed by T with individual yield of 56% and CT is the least with yield of 53%. Model Summary for the optimization of cleanup parameters showed the predicted R-Squared value of 0.972 which is in reasonable agreement with the R-Squared adjusted value of 0.9897. From the results, the application of the DES as solvent for crude oil cleanup was found to be effective with optimal cleanup at run 16.